A potential new pathway for heparin treatment of sepsis-induced lung injury: inhibition of pulmonary endothelial cell pyroptosis by blocking hMGB1-LPS-induced caspase-11 activation - Yang, Rui; Zhang, Xiaojuan (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis is a significant cause of mortality in critically ill patients. Acute lung injury (ALI) is a leading cause of death in these patients. During sepsis, infiltration of protein-rich proinflammatory leukocytes through the broken pulmonary endothelial barrier can result in pulmonary edema and persistent hypoxemia. Endothelial cells exposed to the bacterial endotoxin lipopolysaccharide (LPS) can progress into pyroptosis, a programmed lysis of cell death triggered by inflammatory caspases. Caspase-11 is a cytoplasmic endotoxin LPS receptor that triggers cell pyroptosis. Caspase-11-dependent pyroptosis plays an important role in endotoxemia. Hepatocytes release high mobility group box 1 (HMGB1) that is essential for caspase-11-dependent pyroptosis, and which can lead to mortality during endotoxemia and sepsis. HMGB1 released into the plasma binds to LPS and is internalized into lysosomes in endothelial cells via the advanced glycation end product receptor. In the acidic lysosomal environment, HMGB1 permeates the phospholipid bilayer, which is followed by the leakage of LPS into the cytoplasm and the activation of caspase-11. Heparin is an anticoagulant widely applied in the treatment of thrombotic disease and has been shown to improve the prognosis of ALI during sepsis. Previous studies have found that heparin could block caspase-11-dependent inflammatory reactions, decrease sepsis-related mortality, and reduce ALI, independent of its anticoagulant activity. Heparin or modified heparin with no anticoagulant property could inhibit the alarmin HMGB1-LPS interactions, minimize LPS entry into the cytoplasm, and thus blocking caspase-11 activation. Heparin has been studied in septic ALI, but the regulatory mechanism of pulmonary endothelial cell pyroptosis is still unclear. In this paper, we discuss the potential novel role of heparin in the treatment of septic ALI from the unique mechanism of pulmonary endothelial cell pyroptosis.